Assessment on customer’s accessibility and satisfaction on quality water supply: The case of Magugu water supply authority. - Sixbert, Teresia I. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of Degree of Masters of Business Administration in Corporate Management(MBA-CM) of Mzumbe University